Dampak Sistem Informasi Akuntansi Penjualan dan Pengeluaran Kas Terhadap Pengendalian Internal - Rachmawaty Rachman; Marselly Marselly (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The application of information systems in a business in general can increase competitive advantage by providing added value to the products and services it produces. The application of information systems requires input in the form of data and which will then be processed into information. This information will be needed by the company to assist its operations and also in making decisions. The purpose of this study was to obtain a comprehensive picture of the effect of the Sales and Cash Disbursement Accounting Information System in improving Internal Control. The author in conducting research using descriptive research, using quantitative methods. The researcher uses descriptive research because the questions in this study are asking the relationship between two variables with the questionnaire research data collection procedure (questionnaire) which aims to obtain a clear picture of the research. Where data collection is done through literature, field and questionnaires. Through research conducted by the author, the results obtained include: the results of calculations between the independent variables, namely the Sales Accounting Information System and Cash Expenditures and the dependent variable, namely Internal Control. The results of hypothesis testing in this study indicate that the sales and cash disbursement accounting information system has a significant and positive effect on internal control. Keywords: Accounting Information System, Cash Disbursements, Internal Control